Avidity and Bystander Suppressive Capacity of Human Regulatory T Cells Expressing De Novo Autoreactive T-Cell Receptors in Type 1 Diabetes - Yeh, Wen-I; Seay, Howard R.; Newby, Brittney; Posgai, Amanda L.; Moniz, Filipa Botelho; Michels, Aaron; Mathews, Clayton E.; Bluestone, Jeffrey A.; Brusko, Todd M. (Frontiers in Immunology, 2017)
The ability to alter antigen specificity by T cell receptor (TCR) or chimeric antigen receptor (CAR) gene transfer has facilitated personalized cellular immune therapies in cancer. Inversely, this approach can be harnessed in autoimmune settings to attenuate inflammation by redirecting the specificity of regulatory T cells (Tregs). Herein, we demonstrate efficient protocols for lentiviral gene transfer of TCRs that recognize type 1 diabetes-related autoantigens with the goal of tissue-targeted induction of antigen-specific tolerance to halt β-cell destruction. We generated human Tregs expressing a high-affinity GAD555-567-reactive TCR (clone R164), as well as the lower-affinity clone 4.13 specific for the same peptide. We demonstrated that de novo Treg avatars potently suppress antigen-specific and bystander responder T cell (Tresp) proliferation in vitro in a process that requires Treg activation (P<0.001 versus unactivated Tregs). When Tresp were also GAD-reactive, the high affinity R164 Tregs exhibited increased suppression (P<0.01) with lower Tresp-division index (P<0.01) than the lower-affinity 4.13 Tregs. These data demonstrate the feasibility of rapid expansion of antigen-specific Tregs for applications in attenuating β-cell autoimmunity and emphasize further opportunities for engineering cellular specificities, affinities, and phenotypes to tailor Treg activity in adoptive cell therapies for the treatment of type 1 diabetes.